Reducing Zinc Redistribution and Extending Cycle Life Via Electrochemical Synthesis of Zinc/Zinc Oxide Anodes in Rechargeable Alkaline Batteries. Issue 4 (7th April 2021) - Kolhekar, Snehal; Nyce, Michael; Banerjee, Sanjoy
Abstract : Redistribution of zinc over the electrode surface, also known as shape change, is a major problem and a cause of failure in alkaline zinc anode batteries. To mitigate this phenomenon, we propose a scalable approach based on an in situ formed, highly porous electrochemically synthesized ZnO matrix with uniformly electrodeposited zinc particles. This results in ∼70% improvement in cycle life performance at a rate of 10 mA cm −2 compared to control Zn anodes, which have not gone through the formation process. A quantitative electrolyte analysis revealed under-saturated zincate ion concentration in the electrochemically synthesized ZnO/Zn cells indicating reduced zincate movement. Post mortem analysis of the anodes indicated higher retention of both Zn and ZnO on the electrochemically synthesized ZnO anodes signifying reduced redistribution of active material. Image analysis of the cycled anodes revealed a narrower Zn particle size distribution (62−79 μ m) in contrast to a wider particle size distribution of 51–96 μ m observed in the control anodes. The formation approach results in electrochemically synthesized ZnO/Zn anodes providing a stable ZnO matrix in which Zn particles retain their localized distribution on cycling better than control electrodes conventionally made by pasting zinc particles together with a binder.